Ca2+/Calmodulin-Dependent Protein Kinase II and Androgen Signaling Pathways Modulate MEF2 Activity in Testosterone-Induced Cardiac Myocyte Hypertrophy - Javier Duran; Daniel Lagos; Mario Pavez; Mayarling F. Troncoso; Sebastián Ramos; Genaro Barrientos; Cristian Ibarra; Sergio Lavandero; Sergio Lavandero; Manuel Estrada (Frontiers Media S.A., 2017)
Testosterone is known to induce cardiac hypertrophy through androgen receptor (AR)-dependent and -independent pathways, but the molecular underpinnings of the androgen action remain poorly understood. Previous work has shown that Ca2+/calmodulin-dependent protein kinase II (CaMKII) and myocyte-enhancer factor 2 (MEF2) play key roles in promoting cardiac myocyte growth. In order to gain mechanistic insights into the action of androgens on the heart, we investigated how testosterone affects CaMKII and MEF2 in cardiac myocyte hypertrophy by performing studies on cultured rat cardiac myocytes and hearts obtained from adult male orchiectomized (ORX) rats. In cardiac myocytes, MEF2 activity was monitored using a luciferase reporter plasmid, and the effects of CaMKII and AR signaling pathways on MEF2C were examined by using siRNAs and pharmacological inhibitors targeting these two pathways. In the in vivo studies, ORX rats were randomly assigned to groups that were administered vehicle or testosterone (125 mg⋅kg-1⋅week-1) for 5 weeks, and plasma testosterone concentrations were determined using ELISA. Cardiac hypertrophy was evaluated by measuring well-characterized hypertrophy markers. Moreover, western blotting was used to assess CaMKII and phospholamban (PLN) phosphorylation, and MEF2C and AR protein levels in extracts of left-ventricle tissue from control and testosterone-treated ORX rats. Whereas testosterone treatment increased the phosphorylation levels of CaMKII (Thr286) and phospholambam (PLN) (Thr17) in cardiac myocytes in a time- and concentration-dependent manner, testosterone-induced MEF2 activity and cardiac myocyte hypertrophy were prevented upon inhibition of CaMKII, MEF2C, and AR signaling pathways. Notably, in the hypertrophied hearts obtained from testosterone-administered ORX rats, both CaMKII and PLN phosphorylation levels and AR and MEF2 protein levels were increased. Thus, this study presents the first evidence indicating that testosterone activates MEF2 through CaMKII and AR signaling. Our findings suggest that an orchestrated mechanism of action involving signal transduction and transcription pathways underlies testosterone-induced cardiac myocyte hypertrophy.